Identifying new approaches for U.S. drug policy using ownership, location, and internalization factors - Mariana Saenz; Antony G. Barilla (Review of Economic Analysis (REA), 2020)
Abstract Dunning's Eclectic Paradigm is used to assess the effectiveness and impact of U.S. drug prohibition policy on economic growth and political stability in Latin American countries as well as the decision making of Latin American Transnational Criminal Enterprises (TCE) in the cocaine-coca market. Results showed U.S. drug prohibition policy reduces the on-site supply but does not significantly reduce the transportation of cocaine and coca. U.S. drug prohibition policy also generated political instability for the region, and revealed policy externalities that facilitated TCE expansion. Tougher U.S. drug prohibition policy advances TCE by amplifying the impact that unemployment and local wages have on increases in cocaine-coca production, and by limiting the impact of control of corruption and economic freedom on coca eradication. Our results signal that a site-specific approach accompanied with policies that improve the farmers' economic freedom, such as land formalization rights, and policies that lower unemployment rate facilitate effective U.S. drug prohibition policy.
Keywords: H50; O50; H80; 330; Prohibition; Latin America; Transnational Illegal Enterprises; Dunning's Eclectic Paradigm; Cocaine-Coca Market